Development, validity and reliability testing the Swedish Ethical Climate Questionnaire. (November 2019) - Grönlund, Catarina Fischer; Söderberg, Anna; Dahlqvist, Vera; Andersson, Lars; Isaksson, Ulf
Background: An ethical climate has been described as a working climate embracing shared perceptions about morally correct behaviour concerning ethical issues. Various ethical climate questionnaires have been developed and validated for different contexts, but no questionnaire has been found concerning the ethical climate from an inter-professional perspective in a healthcare context. The Swedish Ethical Climate Questionnaire, based on Habermas' four requirements for a democratic dialogue, attempts to assess and measure the ethical climate at various inter-professional workplaces. This study aimed to present the construction of and to test the psychometric properties of the Swedish Ethical Climate Questionnaire. Method: An expert group of six researchers, skilled in ethics, evaluated the content validity. The questionnaire was tested among 355 healthcare workers at three hospitals in Sweden. A parallel analysis (PA), an exploratory factor analysis and confirmatory factor analysis were performed. Ethical considerations: The participants included in the psychometric analysis were informed about the study, asked to participate in person and informed that they could withdraw at any time without giving any reason. They were also assured of confidentiality in the reporting of the results. Findings: The parallel analysis (PA) recommended one factor as a solution. The initial exploratory factor analysis with a four-factor solution showed low concordance with a four-factor model. Cronbach's alpha varied from 0.75 to 0.82; however, since two factors only consisted of one item, alpha could not be reported. Cronbach's alpha for the entire scale showed good homogeneity (α = 0.86). A confirmatory factory analysis was carried out based on the four requirements and showed a goodness-of-fit after deleting two items. After deletion of these items, Cronbach's alpha was 0.82. Discussion: Based on the exploratory factor analysis, we suggest that the scale should be treated as a one-factor model. The result indicates that the instrument is unidimensional and assesses ethical climate as a whole. Conclusion: After testing the Swedish Ethical Climate Questionnaire, we found support for the validity and reliability of the instrument. We found the 10-item version of Swedish Ethical Climate Questionnaire satisfactory. However, we found no support for measuring different dimensions and, therefore, this instrument should be seen as assessing ethical climate as of whole.